2009
DOI: 10.1016/j.cub.2009.02.056
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Protein Architecture of the Eukaryotic Kinetochore with Nanometer Scale Accuracy

Abstract: Summary The kinetochore is a macromolecular protein machine [1] that links centromeric chromatin to the plus-ends of one or more microtubules (MT), and segregates chromosomes during cell division. Its core structure consists of eight multi-component protein complexes, most of which are conserved in all eukaryotes. We use an in vivo two-color fluorescence microscopy technique to determine, for the first time, the location of these proteins along the budding yeast kinetochore axis at nanometer resolution. Togeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

28
242
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 174 publications
(271 citation statements)
references
References 37 publications
28
242
1
Order By: Relevance
“…The Ndc80 complex hinges about a flexible loop region, and in vitro and in vivo evidence supports the existence of both a folded conformation and an elongated state (8,11). Here, we show that a temperature-sensitive NDC80 mutant (ndc80-121) that has been previously suggested to affect the stability of a folded complex at 37°C exhibits increased microtubule affinity at 37°C compared with the WT complex.…”
Section: Mind Activates Microtubule Binding By Ndc80c Via a Mechanismsupporting
confidence: 61%
See 3 more Smart Citations
“…The Ndc80 complex hinges about a flexible loop region, and in vitro and in vivo evidence supports the existence of both a folded conformation and an elongated state (8,11). Here, we show that a temperature-sensitive NDC80 mutant (ndc80-121) that has been previously suggested to affect the stability of a folded complex at 37°C exhibits increased microtubule affinity at 37°C compared with the WT complex.…”
Section: Mind Activates Microtubule Binding By Ndc80c Via a Mechanismsupporting
confidence: 61%
“…Deleting the loop domain of Ndc80 causes lethality, suggesting that flexibility of the complex is necessary in vivo (12). Additional in vivo evidence suggests that a folded Ndc80 complex is important during early mitosis whereas an elongated conformation exists at metaphase (8)(9)(10). We propose that the Ndc80 complex adopts different conformations to modulate the strength of its microtubule attachment.…”
Section: Mind Activates Microtubule Binding By Ndc80c Via a Mechanismmentioning
confidence: 78%
See 2 more Smart Citations
“…Although numerous immuno-electron microscopy (16)(17)(18) and superresolution microscopy (19)(20)(21) studies have mapped the locations of CCAN components relative to one another, the packing of the chromatin fiber in centrochromatin remains unknown. Early studies of stretched chromosomes suggested a repeating "subunit" structure for the kinetochore (1,22).…”
mentioning
confidence: 99%